Failed diplomacy : the tragic story of how North Korea got the bomb - Pritchard, Charles L. (Washington, D.C. : Brookings Institution Press, 2007)
"Offers an insider's analysis of developments on the Korean peninsula and how North Korea was able to develop nuclear weapons. Provides a first-hand account of how the Six-Party Talks were initiated, with a step-by-step review of each round of negotiations, detailing the national interests of the key players"--Provided by publisher
Preface -- Prelude to crisis -- Part I : The Role of Rhetoric : getting to yes -- Confrontation over highly enriched uranium -- Influencing the Bush team -- Establishing a multilateral framework -- Part II : Origin of the six-party talks -- Washington and Seoul : a falling out -- The players -- Part III : Six-party talks -- Six party talks : a scorecard -- Rounds four and five : false start or cause for optimism? -- Consequences and accountability -- Missiles, nukes, and talks -- Bilateral engagement with Pyongyang : the record -- Establishing a permanent security forum -- Epilogue -- Appendix A -- Appendix B -- Appendix C -- Appendix D -- Notes -- Index.
Includes bibliographical references (pages 205-218) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Nuclear nonproliferation -- Korea (North); Nuclear weapons -- Korea (North); United States -- Foreign relations -- Korea (North); Korea (North) -- Foreign relations -- United States; Non-prolifération nucléaire -- Corée du Nord; Armes nucléaires -- Corée du Nord; États-Unis -- Relations extérieures -- Corée du Nord; HISTORY -- Military -- Nuclear Warfare; POLITICAL SCIENCE -- Security (National & International); Diplomatic relations; Nuclear nonproliferation; Nuclear weapons; Korea (North); United States; Kernwapens; Buitenlandse politiek; Diplomatieke betrekkingen; Onderhandelingen; Noord-Korea.; Verenigde Staten; Rüstungspolitik; Außenpolitik; Nordkorea; USA; Nuclear nonproliferation -- Korea (North); Nuclear weapons -- Korea (North); United States -- Foreign relations -- Korea (North); Korea (North) -- Foreign relations -- United States; North Korea; United States of America; Nuclear weapons; Proliferation, non-proliferation.; Diplomacy; International relations; Foreign policy; Kärnvapenspridning -- Nordkorea; Förenta staterna -- diplomatiska förbindelser -- Nordkorea; Nordkorea -- diplomatiska förbindelser -- Förenta staterna; Kernwaffe -- Rüstungspolitik.; Geschichte 2002-2006